Knowledge society versus the neoliberalist model (Revista Electrónica REDINE, 2020)
In the educational system it is essential to exchange and share knowledge, for this, the introduction of Information and Communication Technologies (ICT) such as the internet; They play an important role, since the digital divide between people who have similar interests is reduced and that in turn give effective use to develop this knowledge. In this argumentative essay, it is pondered how knowledge societies are built based on an educated population, with knowledge-producing institutions, without the influence of neoliberalism, because both are two very dissimilar spheres. UNESCO's mission is to develop education as an essential right, improve the quality of education and stimulate innovation and political dialogue, hence, educational institutions are producers and generators of knowledge, becoming the most important capital where the success of a society resides in its benefit. There is no doubt that knowledge has become the center of political, cultural and economic challenges, where the societies whose prospects are beginning to be perceived can be classified as knowledge societies.